The influence of defender`s positional gap on the aces in the sport of volleyball - Anlvares Denardi, R.; Romero, F.; Costa Oliveira, T. A.; Silva, S. L.; Travassos, B.; Cesar Corrêa, U. (Journal of Human Sport & Exercise, 2017)
This study aimed to investigate the influence of the defending players' positioning on the service outcomes. Thirty-nine sequences of play involving serves were selected from nine games of a Professional Championship of volleyball held in Brazil. They characterized three main situations: (a) aces (serves that the ball hit the ground of the opponent's court without being touched by any defending player) (n = 13), (b) serves which a defending player touched the ball but there was no continuity in the rally (n = 13), and (c) serves received successfully, that is, a defender received the ball and made possible the continuity of the rally (n = 13). These situations were compared by considering the following variables: (1) defender`s distance to the place of serve finalization, (2) velocity of defender's displacement to the place of serve finalization; (3) variability of defending player`s displacement; and, (4) serve velocity. Results showed that the defender`s distance to the place of serve finalization in the aces were greater than in the both other situations. The findings allowed us to conclude that in competitive performances in the sport of volleyball, the defender`s distance to the place of serve finalization determined the service outcomes.